2020
DOI: 10.1021/acscentsci.0c00822
|View full text |Cite
|
Sign up to set email alerts
|

Sinter-Resistant Nanoparticle Catalysts Achieved by 2D Boron Nitride-Based Strong Metal–Support Interactions: A New Twist on an Old Story

Abstract: Strong metal–support interaction (SMSI) is recognized as a pivotal strategy in hetereogeneous catalysis to prevent the sintering of metal nanoparticles (NPs), but issues including restriction of supports to reducible metal oxides, nonporous architecture, sintering by thermal treatment at >800 °C, and unstable nature limit their practical application. Herein, the construction of non-oxide-derived SMSI nanocatalysts based on highly crystalline and nanoporous hexagonal boron nitride (h-BN) 2D materials was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…Strong metal–support interaction (SMSI) construction is a pivotal strategy in heterogeneous catalysis to afford supported metal nanocatalysts with thermally robust and sintering-resistant properties and regulate the catalytic activities and selectivities (e.g., in hydrogenation reactions). Since the pioneering work of Tauster et al, , the following approaches have been demonstrated for SMSI construction: high-temperature treatment (>300 °C) of metal nanoparticles (NPs) supported on reducible metal oxide carriers in a reducing atmosphere (e.g., H 2 ) or phosphates, hydroxyapatite, and ZnO in an oxidizing atmosphere (e.g., O 2 ), a sacrificial carbon coating strategy (500–700 °C), , and hexagonal boron nitride (h-BN) based systems (750–850 °C). , So far, SMSI construction has been achieved only via thermally induced reactions (>300 °C) in specific gaseous atmospheres, inducing redox interactions and encapsulation between the carriers and the metal NPs (Table S1 and Supplementary Content (SC)-1). To date, limited methodologies capable of introducing SMSI at relatively low heating temperatures have been developed.…”
mentioning
confidence: 99%
“…Strong metal–support interaction (SMSI) construction is a pivotal strategy in heterogeneous catalysis to afford supported metal nanocatalysts with thermally robust and sintering-resistant properties and regulate the catalytic activities and selectivities (e.g., in hydrogenation reactions). Since the pioneering work of Tauster et al, , the following approaches have been demonstrated for SMSI construction: high-temperature treatment (>300 °C) of metal nanoparticles (NPs) supported on reducible metal oxide carriers in a reducing atmosphere (e.g., H 2 ) or phosphates, hydroxyapatite, and ZnO in an oxidizing atmosphere (e.g., O 2 ), a sacrificial carbon coating strategy (500–700 °C), , and hexagonal boron nitride (h-BN) based systems (750–850 °C). , So far, SMSI construction has been achieved only via thermally induced reactions (>300 °C) in specific gaseous atmospheres, inducing redox interactions and encapsulation between the carriers and the metal NPs (Table S1 and Supplementary Content (SC)-1). To date, limited methodologies capable of introducing SMSI at relatively low heating temperatures have been developed.…”
mentioning
confidence: 99%
“…h‐BN is another two‐dimensional nanomaterial which have a multilayer structure similar to graphene, with a hexagonal honeycomb network composed of B−N bonds [31,32] . The flake h‐BN is selected as the substrate to support metal oxide nanoparticles, so that the nanoparticles are uniformly dispersed on the h‐BN surface [33,34] . It solved the problem of aggregation and sedimentation caused by the size of the nanoparticles, generating a synergistic effect to improve the performance of the composite simultaneously [1] …”
Section: Introductionmentioning
confidence: 99%
“…[31,32] The flake h-BN is selected as the substrate to support metal oxide nanoparticles, so that the nanoparticles are uniformly dispersed on the h-BN surface. [33,34] It solved the problem of aggregation and sedimentation caused by the size of the nanoparticles, generating a synergistic effect to improve the performance of the composite simultaneously. [1] But h-BN have light absorption just in UV region, which restricts its development in the field of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Metal sintering and loss or coke deposition are challenges for metal catalysts in many reactions, which could be solved by constructing metal@ h- BN nanostructures as well. The chemically and thermally stable h- BN shells provide better protection on metal NPs from agglomeration, leaching, and oxidation than other encapsulation materials, like carbon nanotubes or graphene, especially in strong acidic media or oxidizing atmospheres. , For example, the as-prepared Ni@ h- BN nanocatalysts exhibit high thermal stability and sintering resistance to withstand thermal treatments up to 950 °C . The ultrastable catalysts can work for CO oxidation with impurities of moisture or hydrocarbons.…”
mentioning
confidence: 99%
“…89,90 For example, the as-prepared Ni@h-BN nanocatalysts exhibit high thermal stability and sintering resistance to withstand thermal treatments up to 950 °C. 91 The ultrastable catalysts can work for CO oxidation with impurities of moisture or hydrocarbons. Because of the weakening dissociation ability of gases under h-BN cover, there is much less coke deposition in syngas methanation reaction (Figure 6d) by Ni catalysts 84 and methane partial oxidation by Rh catalysts, 92 leading to a steady performance in long-term operation.…”
mentioning
confidence: 99%